Factors influencing reuse intention of e-payment in Thailand: A case study of promptpay - Ladkoom, Kobthong; Thanasopon, Bundit (My University, 2020)
Thai e-commerce is growing rapidly in the past few years. The driving factors for the rapid growth arise from increased Internet and mobile phone use as well as improved e-payment and logistics. Thai government has come up with a national e-payment initiative called “PromptPay” with an aim to reduce the use of cash and catalyze the adoption of e-payment in Thailand. However, the use of e-payment in Thailand is still lagged behind other countires. The objective of this research is therefore to identify factors influencing reuse intension of e-payment in Thailand and their antecedents. For our preliminary study, we survey PromptPay 100 users in Bangkok and analyze the data using PLS-SEM technique. The results suggest that satisfaction and attitude positively impact reuse intention of PromptPay. In addition, perceived usefulness is found to be a driver of user satisfaction and positive attitude towards PromptPay, while positive confirmation affects satisfaction. However, trust is unexpectedly found to be insignificant to reuse intention of PromptPay. Our proposed conceptual model offers an alternative model studying e-payment adoption in other context, while our findings could help Thai government in planning their strategy for improving the diffusion rate of PromptPay in Thailand.
Keywords: Attitude; Concern for Information Privacy (CFIP); Confirmation; Consumer's Liability; E-Payment; Perceived Usefulness; PLS-SEM; Privacy Risk; Reuse Intention; Risk Acceptability; Satisfaction; TAM; Trust